Nucleus Accumbens Deep Brain Stimulation for Alcohol Addiction – Safety and Clinical Long-term Results of a Pilot Trial - Müller, U. J.; Sturm, V.; Voges, J.; Heinze, H.-J.; Galazky, I.; Büntjen, L.; Heldmann, M.; Frodl, T.; Steiner, J.; Bogerts, B. (Pharmacopsychiatry, 2016)
We report on the long-term clinical outcome (up to 8 years) of 5 patients who received deep brain stimulation (DBS) of the nucleus accumbens to treat their long-lasting and treatment-resistant alcohol addiction. All patients reported a complete absence of craving for alcohol; 2 patients remained abstinent for many years and 3 patients showed a marked reduction of alcohol consumption. No severe or long-standing side effects occurred. Therefore, DBS could be a promising, novel treatment option for severe alcohol addiction, but larger clinical trials are needed to further investigate the efficacy of DBS in addiction.
Keywords: alcohol addiction; deep brain stimulation; nucleus accumbens; craving